Prevalence of visual impairment and refractive error in school-aged children in South Darfur State of Sudan - Saif H. Alrasheed; Kovin S. Naidoo; Peter C. Clarke-Farr (African Vision and Eye Health, 2016)
Background: Global estimates suggest there are almost 19 million visually impaired children worldwide, the major cause being uncorrected refractive error (RE).